EXAMINING THE LEVEL OF COMPLIANCE WITH IND AS IN NIFTY 50 COMPANIES: A CASE STUDY APPROACH - N, Mamatha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study examines the level of compliance with Indian Accounting Standards (Ind AS) among Nifty 50 companies, focusing on their transition from the Indian Generally Accepted Accounting Principles (IGAAP) to the Ind AS framework. Ind AS, aligned with International Financial Reporting Standards (IFRS), was introduced to enhance transparency, comparability, and accountability in financial reporting. The Nifty 50, representing the 50 largest publicly listed companies in India, serves as a critical benchmark for evaluating the adoption and implementation of these standards in India's corporate sector. The study delves into key areas of compliance, including revenue recognition, financial instruments, lease accounting, and foreign exchange transactions. By analyzing financial statements, audit reports, and disclosures, the study assesses the challenges and benefits faced by these companies during the transition process. Key challenges identified include the complexity of fair value accounting, the shift to an expected credit loss model for financial instruments, and the reclassification of leases under Ind AS 116. The findings indicate that while most Nifty 50 companies have successfully adopted Ind AS, challenges persist in terms of consistent application, system upgrades, and employee training. The study highlights the overall positive impact of Ind AS adoption on financial transparency and investor confidence, despite initial hurdles. It concludes that compliance with Ind AS has significantly improved the quality of financial reporting among Nifty 50 companies, aligning them with global best practices and enhancing their credibility in the international financial markets.